Dapagliflozin as add‐on therapy in Asian patients with type 2 diabetes inadequately controlled on insulin with or without oral antihyperglycemic drugs: A randomized controlled trial1: 达格列净联合胰岛素治疗无论是否使用口服降糖药均血糖控制不佳的亚洲2型糖尿病患者:一项随机对照试验. Issue 7 (25th January 2018) - Yang, Wenying; Ma, Jianhua; Li, Yiming; Li, Yanbing; Zhou, Zhiguang; Kim, Jae Hyeon; Zhao, June; Ptaszynska, Agata
Abstract: Background: This 24‐week Phase 3 double‐blind placebo‐controlled study assessed the safety and efficacy of dapagliflozin as add‐on to insulin, with or without oral antihyperglycemic drugs (OADs), in Asian patients with inadequately controlled type 2 diabetes mellitus. Methods: Adult patients with HbA1c between ≥7.5% and ≤10.5%, body mass index ≤45 kg/m 2, and on insulin doses ≥20 IU daily were randomized to dapagliflozin 10 mg ( n = 139) or placebo ( n = 133) to assess 24‐week changes in HbA1c (primary outcome), fasting plasma glucose (FPG), body weight, total daily dose of insulin (TDDI), and seated systolic blood pressure (SeSBP; exploratory outcome). Results: Baseline characteristics were similar in both groups. At Week 24, compared with placebo, dapagliflozin significantly improved HbA1c (mean [95% confidence interval] 0.03% [−0.11, 0.17] for placebo vs −0.87% [−1.00, −0.74] for dapagliflozin; between‐group difference − 0.90% [−1.09, −0.71], P < 0.0001]), FPG, body weight, TDDI, and SeSBP. The incidence of adverse events (AEs) in the dapagliflozin and placebo groups was 80.5% and 71.2%, respectively, with few patients discontinuing due to AEs (dapagliflozin, 2.2%; placebo, 4.2%). The occurrence of hypoglycemia was similar in the dapagliflozin and placebo groups (23.7% and 22.6%, respectively; no major events). The frequency of urinary tract and genital infections was low; no deaths were reported. Conclusions: Dapagliflozin as add‐on to insulin, with or without OADs, significantly improved glycemic control and reduced body weight and blood pressure in Asian patients. Dapagliflozin was well tolerated, with a similar frequency of hypoglycemia in both groups. These results support the use of dapagliflozin as add‐on to insulin, with or without OADs, in this population. Abstract : Highlights This 24‐week, Phase 3 double‐blind placebo‐controlled study assessed the safety and efficacy of dapagliflozin as add‐on to insulin, with or without oral antihyperglycemic drugs, in Asian patients with inadequately controlled type 2 diabetes mellitus. Study results demonstrate that compared with placebo, dapagliflozin 10 mg as add‐on to insulin, with or without oral antihyperglycemic drugs, significantly improved glycemic control and reduced body weight and blood pressure, without increased risk of hypoglycemia.